Rheological properties of activated sludge in a sMBR - Hasar, H; Kinaci, C; Ünlü, A; Togrul, H; Ipek, U (Elsevier Science Sa, 2004)
In this work, the main objective was to conduct a study on the flow model of the sludge produced in a submerged membrane bioreactor (sMBR). For this purpose, the sludge samples were drawn from a bioreactor, including various solid contents. The relationship between shear rate and shear stress of the samples was determined by using a rotary viscometer. The effects of temperature and solid concentration on the rheology of the sludge were also investigated. It was found that the best flow model for the samples was the Ostwald de Vaele model. The apparent viscosity decreased logarithmically with an increase in the rotary velocity and increased exponentially with an increase in the solid content of sludge. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: submerged membrane bioreactor; rheology; non-Newtonian fluids; viscosity